Proceso de atención nutricional en paciente de sexo femenino de 21 años de edad con embarazo gemelar de 23 semanas de gestación con sobrepeso e hipertensión gestacional. - Vargas Coello, Linda María (2022)
The present case study whose realization entails a theoretical and practical orientation, consists of the nutritional assessment of a 21-year-old female patient with a twin pregnancy of 23 weeks of gestation who presents signs and symptoms of gestational hypertension. However, the pertinent medical studies and the evaluation of the nutritional status were carried out using the four methods: anthropometric, biochemical, clinical and dietary; through which the patient was diagnosed with overweight and inadequate weight gain due to excess for her nutritional status. After obtaining all the data required from the patient, the nutritional treatment was carried out, which consisted in the design of a balanced diet plan in energy, macronutrients and essential micronutrients during pregnancy. It should be noted that the energy was increased with respect to what is included in the clinical practice guidelines of the Ministry of Public Health that deals with food and nutrition in pregnant women. In turn, the respective follow-up was carried out for one month to verify that the nutrition and diet therapy prescription had the expected effect. Despite being a short time to carry out a monitoring, the changes could be evidenced, for example; a weight gain of 3 kilograms and a better choice of food considering their needs, tastes and food preferences.